The guidelines of parameters in the implementation of local monocular vision system for robot soccer using the mirosot platform - S. Nadarajah, Sivadev (School of Mechatronic Engineering, 2016)
The research objectives are to compare between the displaying of videos in two modes, the full video mode and the split video mode and obtain a mode that is fastest in terms of frame rate; to compare the efficiency in terms of frame rate between the option to display the videos and to not display the videos for both full video and split video mode; to apply the calibration based distance estimation technique and determine its accuracy on the system; to test other different color models, namely YUV and HSV, based on the results a comparison between YUV, HSV and RGB will be done to determine which is more efficient in terms of frame rate and to propose the guideline of parameters for the implementation of local monocular vision system in robot soccer.